2015
DOI: 10.1371/journal.pone.0142722
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in a Cohort of Patients Started on Antiretroviral Treatment and Followed up for a Decade in an Urban Clinic in Uganda

Abstract: BackgroundShort-medium term studies from sub-Saharan Africa show that, despite high early mortality, substantial loss to program, and high rates toxicity, patients on antiretroviral treatment have achieved outcomes comparable to those in developed settings. However, these studies were unable to account for long term outcomes of patients as they stayed longer on treatment.ObjectivesWe aim to describe ten years outcomes of one of the first cohort of HIV positive patients started on antiretroviral treatment (ART)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 16 publications
5
26
1
Order By: Relevance
“…This explains the progressive increase in CD4+ T cells observed from one year to the other in all three groups of patients of this study. This result is consistent with a study carried out in an Ugandan cohort where CD4+ T cell levels increased continuously throughout the 10-year follow-up, and 83.8% of the patients reached CD4+ T cell amounts above the lower reference value 19 . In an Asian study with 6,521 HIV-1-infected patients, there was a positive increase over time in CD4+ T cells gains and in the proportion of patients with VL suppression 20 .…”
Section: Virologic Response/initialsupporting
confidence: 92%
“…This explains the progressive increase in CD4+ T cells observed from one year to the other in all three groups of patients of this study. This result is consistent with a study carried out in an Ugandan cohort where CD4+ T cell levels increased continuously throughout the 10-year follow-up, and 83.8% of the patients reached CD4+ T cell amounts above the lower reference value 19 . In an Asian study with 6,521 HIV-1-infected patients, there was a positive increase over time in CD4+ T cells gains and in the proportion of patients with VL suppression 20 .…”
Section: Virologic Response/initialsupporting
confidence: 92%
“…When those who transferred out of the facility are excluded, ten‐year mortality is slightly higher at 25.4% and LTF, although still in range compared to other studies, is also higher at 39.6%. Lower rates of mortality and LTF seen in some studies may be the result of intensive monitoring and enhanced patient retention interventions, including counselling, appointment reminders and active tracing . Additionally, linking our mortality data to the VRS would have resulted in higher mortality than observed in patient files, as demonstrated by previous work done by our group that found that 37% of those lost to follow‐up had actually died .…”
Section: Discussionmentioning
confidence: 64%
“…This 12-month retention rate is comparable to the 77% summarized retention in a meta-analysis using 2008 to 2013 LMIC data [38]. Few sub-Saharan African studies have reported data on longterm ART outcomestwo from Nigeria (ten-and seven-year follow-up), one from Uganda (ten-year follow-up), one from Zimbabwe (ten-year follow-up), one from Mozambique (nineyear follow-up) and one from South Africa (twelve-year followup) [23][24][25][26][27][28]. These studies show mixed results, with retention ranging from 37% to 83%, mortality from 1% to 24% and LTF from 5% to 51%; our observed ten-year 18.5% mortality and 28.8% LTF from the initiating clinic lie within these ranges "Yes, they give me a counselling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If ART suppression or re-suppression rates are high (i.e., ART failure is less common), the value of more accurate but more costly monitoring strategies, such as VL, is reduced [26]. In Mozambique, 19–24% of patients on 1 st -line ART have evidence of virologic failure [27,28], similar to other settings in sub-Saharan Africa [29,30]; while scale-up of ART coverage continues, investment in longitudinal care is essential to maintain virologic suppression, gain long-term benefits of ART, and reduce transmissions and deaths.…”
Section: Discussionmentioning
confidence: 99%